Acute Gouty Arthritis with Knee Effusion in a Patient with Chronic Lymphocytic Leukemia: Diagnostic Confirmation and Pre-Chemotherapy Hyperuricemia Management - Panji Hadi Permana; Eka Kurniawan; Raveinal; Deka Viotra; Fadrian Fadrian (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Gout and chronic lymphocytic leukemia (CLL) represent distinct hematologic and rheumatologic pathologies; however, their concurrent presentation presents significant diagnostic and therapeutic challenges. Tumor lysis syndrome and chemotherapy-induced hyperuricemia are recognized complications of hematologic malignancies, yet the manifestation of acute gouty arthritis with crystallographic confirmation in CLL patients remains an underreported clinical scenario requiring careful diagnostic stratification. Case presentation: We present a 69-year-old male farmer with newly diagnosed CLL (stage C, Binet classification) admitted for acute left knee arthritis with effusion, left ankle arthritis, and concurrent community-acquired pneumonia (CAP). Clinical examination revealed articular inflammation characterized by pain, swelling, erythema, warmth, and significant joint effusion with documented flexion limitation and positive bulging sign. Musculoskeletal ultrasound demonstrated double contour sign, synovial hypertrophy, and effusion measuring 5.8 cm in the suprapatellar recess with monosodium urate (MSU) crystal deposition confirmed by polarized light microscopy of synovial fluid (5,350 cells/mm³, 40% polymorphonuclear neutrophils, 60% mononuclear cells, positive MSU crystals). Serum uric acid was elevated at 10.6 mg/dL. The patient was successfully managed with colchicine, methylprednisolone, arthrocentesis, and supportive care while maintaining CLL treatment preparedness. Conclusion: This case illustrates the importance of confirmatory synovial fluid analysis and ultrasound imaging in the diagnosis of acute gout in the context of hematologic malignancy. Optimal management requires careful coordination between rheumatology and hematology-oncology services to prevent therapeutic complications and ensure safe chemotherapy initiation in CLL patients with concurrent acute gouty arthritis and hyperuricemia.